Recognition and management of pain in cattle - Hudson, C.D.; Whay, H.R.; Huxley, J.N. (BMJ Publishing Group, 2008)
Attitudes towards pain and its control in farm animals have lagged behind those in companion animal species. However, a considerable amount of work over the past 15 years has focused on the perception of pain in cattle based on objective and subjective assessment by clinicians working with this species. A recent large-scale survey of cattle practitioners revealed that over half of the respondents felt their knowledge of pain and analgesia in cattle was inadequate or could be improved, and the majority of these identified a lack of readily available information on the subject as being a contributory factor. This article reviews current knowledge on pain assessment in cattle in a clinical setting, and discusses some protocols for pain management in specific conditions.